Pengembangan Sereal Sarapan Tersubstitusi Bekatul dan Tepung Pisang - Sukarno Sukarno; Dwyana Izza Augusta; Azis Boing Sitanggang; Afwa Nururrahmah Munawaroh; Slamet Budijanto (Jurnal Ilmu Pertanian Indonesia, 2022)
Rice bran and banana flour contain nutrients and bioactive compounds that have potential to be used for the development of functional food, such as breakfast cereal. The study is aimed to develope functional breakfast cereal from corn flour (54%, 59%, 64%), rice bran (20%), and banana flour (10%) (raja bandung and kepok) with the addition of coconut sugar (0 %, 5 %, 10%) using twin-screw extruder. The best-accepted formula based on sensory test was cereal with the substitution of 0% coconut sugar and 10% raja bandung banana flour. The breakfast cereal has moisture content of 10.38 ± 0.01%, ash content of 3.36 ± 0.00%, protein content of 8.92 ± 0.11%, fat content of 6.14 ± 0.07%, carbohydrate content of 81.58 ± 0.18%, and dietary fiber content of 13.22 ± 0.46% which can be claimed as high-fiber foods. It contained a total phenol content of 74.13 ± 0.87 mg GAE / 100 g, antioxidant activity of 40.67 ± 1.71 mg AEAC/ 100 g, and IC50 of 84.48 ± 0.9 mg/mL. Saturated fatty acids in breakfast cereal were dominated by palmitic acid (14.22 ± 0.17%), while for unsaturated fatty acids were dominated by oleic acid (30.76 ± 0.04%) and linoleic acid (45.40 ± 0.03%). Keywords: banana flour, breakfast cereal, functional food, rice bran